Antibacterial effect of flavonoids in castanea mollissima blume on common spoilage bacteria in low-temperature meat products. Issue 1 (May 2020) - Zhang, Wenyu; Wu, Zhumeng; Wang, Xiaoyue; Li, Xiaoyan; Ma, Dongshuo; Wang, Fang; Qi, Jinghua; Pang, Meixia
Abstract: The oxford cup method and filter paper method were used to determine the antibacterial effect of flavonoids extracted from castanea mollissima blume, three kinds of common spoilage bacteria in low-temperature meat products were subjects to be tested, named proteus, macrococcus and bacillus. The results showed that flavonoids in castanea mollissima blume had an antibacterial effect on proteus and macrococcus. For flavonoid glycosides, the diameters of inhibition zone were 16.32 mm and 17.76 mm, and the minimum inhibitory concentration were 0.00625 g/mL and 0.0125 g/mL, respectively. The effective inhibitory time was 14 h. For free flavonoids, the maximum diameter of the inhibition zone was 7 mm, the minimum inhibitory concentration was 0.0125 g/mL. They had no antibacterial effect on bacillus. As natural bacteriostatic agents, the flavonoids in castanea mollissima blume are likely to have many important applications in meat products in the future.